Comparing Optimal Portfolio Performance Based on Skew-Normal Distribution and Skew-Laplace-Normal Distribution: A Mean-Absolute Deviation-Entropy Approach - Hila Rezaei; Gholamhossien Golarzi; Omid Karimi (مدیریت صنعتی)
Objective Investors typically seek to strike the optimal balance between potential returns and associated risks in their trades. Various models have been presented to choose the optimal portfolio using different approaches. one of these methods is based on the statistical distribution of asset return. In these methods, the type of distribution of returns is first identified, and a suitable portfolio selection method is then applied based on this identified distribution type. This study compares the effectiveness of the mean-absolute deviation-entropy model utilizing both Skew-Normal Distribution and Skew-Laplace-Normal Distribution for constructing an optimal portfolio in the Tehran Stock Exchange over 36 months from April 2018 to March 2020.